Comparison of decision methods to initiate fungicide applications against cercospora blight of carrot - Abraham, V.; Kushalappa, A.C.; Carisse, O.; Bourgeois, G.; Auclair, P. (Phytoprotection, 1995)
In 1991 and 1992, two thresholds of a forecasting model were compared with two other decision methods for effectiveness in timing the first fungicide application against Cercospora blight of carrot induced by Cercospora carotae. The first fungicide application was made when : 1) the plants reached 15 cm in height (conventional method); 2) the intermediate (middle) leaves of 50% of the plants were diseased (50% disease incidence threshold method); 3) the cumulative infection equivalence (CE) was 14 (forecasting model CE 14); and 4) the CE was 18 (forecasting model CE 18). In all four treatments, subsequent applications of fungicide were made at 10-d intervals when there was no rain, and at 7-d intervals when there was rain. The CE was calculated based on duration of leaf wetness and temperature during the wet period, corrected for high humidity and interrupted wet periods, and was cumulative starting at crop emergence. For thresholds of CE 14 and CE 18, no yield losses were observed and the total number of fungicide applications needed was lower compared to conventional and 50% disease incidence threshold methods. In a separate study, the CE thresholds were related to the percentage of commercial fields that reached disease incidence thresholds of 50, 80 and 100% to establish low risk (CE 11-15) and high risk (CE 16-20) thresholds. The forecasting of low and high risk CE thresholds were too late for 3 and 19% of the commercial fields because those fields had more than 50 and 80% of the plants diseased, respectively.